On the Exact Finite Sample Distribution of the L1 -FCvM Test Statistic - Jeroen Hinloopen (Tinbergen Institute, 2011)
We derive the exact finite sample distribution of the L1-version ofthe Fisz-Cramér-von Mises test statistic (L1-FCvM). We first characterizethe set of all distinct sample p-p plots for two balanced sampleof size n absent ties. Next, we order this set according to the correspondingvalue of L1-FCvM. Finally, we link these values to theprobabilities that the underlying p-p plots emerge. Comparing the finitesample distribution with the (known) limiting distribution showsthat the latter can always be used for hypothesis testing: although forfinite samples the critical percentiles of the limiting distribution differfrom the exact values, this will not lead to differences in the rejectionof the underlying hypothesis.
Keywords: C12; C14; C46; 330; Sample p-p plot; EDF test; finite sample distribution; limiting distribution; Statistische Verteilung; Statistischer Test; Theorie